A fully bio-based polyimine vitrimer derived from fructose. Issue 7 (12th March 2019) - Dhers, Sébastien; Vantomme, Ghislaine; Avérous, Luc
Abstract : A bio-based polyimine vitrimer containing 100% renewable carbon content has been synthesised and characterised, based on bio-based furan dialdehyde derived from fructose. Abstract : A bio-based polyimine vitrimer containing 100% renewable carbon content has been synthesised and characterised. This vitrimer material was prepared by combining a bio-based furan dialdehyde obtained from fructose with a bio-based diamine and triamine prepared from fatty acids. Due to the dynamic nature of the imine reversible bonds, the vitrimer properties can be clearly demonstrated. The obtained films exhibit fast stress relaxation around room temperature. To the best of our knowledge, this is the first report of a fully bio-based polyimine vitrimer.